Denosumab as the Treatment of Recalcitrant Tuberculous Pleural Effusion-Associated Hypercalcemia - Afdhal Afiq Abd Jalil; Sharifah Faradila Wan Muhamad Hatta; Aimi Fadilah Mohamad; Mohammed Fauzi Abdul Rani (Case Reports in Medicine)
Denosumab is a human monoclonal antibody that binds to RANKL (receptor activator of nuclear factor-kappa B ligand). It has mainly been used in the treatment of osteoporosis for a variety of causes especially in situations refractory to bisphosphonates or when kidney function is impaired. It is also used in cases of malignancy-associated hypercalcemia. There are many causes of hypercalcemia, but only rarely it is associated with granulomatous diseases such as tuberculous pleural effusion. We report a case of hypercalcemia from tuberculous pleural effusion that was initially admitted with left medium abundance pleural effusion and a serum corrected calcium level of 3.48 mmol/L. The calcium level was successfully normalized within 72 hours of subcutaneous denosumab administration after other interventions have failed.